Pengaruh Pemahaman Investasi, Teknologi Informasi dan Literasi Keuangan Terhadap Minat Investasi Mahasiswa - Anisa Rizqi Artanti; Riskin Hidayat (Departemen Manajemen, 2023)
Abstract: This research was conducted in order to be able to detect the impact of investment understanding, information technology, and financial literacy on the investment interest of YPPI University students in Rembang. The nature of the research used is quantitative based on primary data by distributing questionnaires. The population used is students majoring in Management and Accounting with a total of 366 students. Stratified Random sampling is a technique used for sampling. And for samples used a total of 100. The data processing technique used is the multiple linear regression method. The results of this study indicate that these three variables have a significant positive influence on the investment interest of YPPI Rembang University students.